A new organocatalytic desymmetrization reaction enables the enantioselective total synthesis of madangamine E - Shiomi, S; Shennan, BDA; Yamazaki, K; Fuentes de Arriba, ÁL; Vasu, D; Hamlin, TA; Dixon, DJ (American Chemical Society, 2022)
The enantioselective total synthesis of madangamine E has been completed in 30 steps, enabled by a new catalytic and highly enantioselective desymmetrizing intramolecular Michael addition reaction of a prochiral ketone to a tethered β,β′-disubstituted nitroolefin. This key carbon–carbon bond forming reaction efficiently constructed a chiral bicyclic core in near-perfect enantio- and diastereo-selectivity, concurrently established three stereogenic centers, including a quaternary carbon, and proved highly scalable. Furthermore, the pathway and origins of enantioselectivity in this catalytic cyclization were probed using density functional theory (DFT) calculations, which revealed the crucial substrate/catalyst interactions in the enantio-determining step. Following construction of the bicyclic core, the total synthesis of madangamine E could be completed, with key steps including a mild one-pot oxidative lactamization of an amino alcohol, a two-step Z-selective olefination of a sterically hindered ketone, and ring-closing metatheses to install the two macrocyclic rings.